Penerapan Metode Talking Stick Untuk Meningkatkan Keaktifan Siswa dalam Pembelajaran IPAS Kelas 5 di SDN 42 Pekanbaru - Novi Astari; Fitriyeni (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to enhance student activeness in IPAS learning through the implementation of the Talking Stick method in fifth-grade students at SDN 42 Pekanbaru. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of the planning, implementation, observation, and reflection stages. Data were collected through observations, questionnaires, and documentation, then analyzed to determine the level of teacher and student activeness during the learning process. Findings from Cycle I show that student activeness reached the "Fairly Active" category, with observation results of 59.13% and questionnaire results of 59.75%. After improvements were applied in Cycle II, student activeness increased significantly, reaching 91.48% in observations and 96.79% in questionnaires, both categorized as "Very Active." Teacher activeness also reached 100% in Cycle II. These results indicate that the Talking Stick method fosters a more interactive learning atmosphere, encourages equal participation, increases students’ confidence, and strengthens learning motivation. Therefore, the Talking Stick method is effective as a learning strategy to enhance student activeness in IPAS subjects.